Breaking the histone code with quantitative mass spectrometry. (October 2011) - Britton, Laura-Mae P; Gonzales-Cope, Michelle; Zee, Barry M; Garcia, Benjamin A
Histone post-translational modifications (PTMs) comprise one of the most intricate nuclear signaling networks that govern gene expression in a long-term and dynamic fashion. These PTMs are considered to be 'epigenetic'' or heritable from one cell generation to the next and help establish genomic expression patterns. While much of the analyses of histones have historically been performed using site-specific antibodies, these methods are replete with technical obstacles (i.e., cross-reactivity and epitope occlusion). Mass spectrometry-based proteomics has begun to play a significant role in the interrogation of histone PTMs, revealing many new aspects of these modifications that cannot be easily determined with standard biological approaches. Here, we review the accomplishments of mass spectrometry in the histone field, and outline the future roadblocks that must be overcome for mass spectrometry-based proteomics to become the method of choice for chromatin biologists.